Pengaruh Total Quality Management, Sistem Pengukuran Kinerja, Sistem Penghargaan, dan Komitmen Organisasi Terhadap Kinerja Manajerial (Studi Kasus pada Perusahaan Batik Danar Hadi) - Wulandari, Dika Ayu, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
This research aims to know the influence of total quality management, performance measurement system, system of reward, and organizational commitment to managerial performance. The object of this research is PT. Batik Danar Hadi. The sampling method used total sampling (samples using all members of the population). The number of respondents who participated in this research is 42 manager. Techniques and methods of data analysis used in this study using multiple linear regression analysis with the help of SPSS 16 program. The result of this research showed that total quality management, system of reward, and organizational commitment influences to managerial performance, whereas the performance measuremeant system does not influence managerial performance. Keywords: total quality management, performance measurement system, system of reward, organizational commitment.